Preferensi Wisatawan terhadap Keindahan Lanskap Akomodasi Berbasis Vegetasi Di Gili Meno, Nusa Tenggara Barat - Mardiyanto Rahayu, Slamet; Fathurrahman; Aminy, Muhammad Habibullah (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2023)
Gili Meno is one of the popular tourist destinations in West Nusa Tenggara. On Gili Meno there are many accommodation landscapes. This study aims to determine tourist preferences for the accommodation landscape in Gili Meno, West Nusa Tenggara. The research was conducted by purposive sampling. Questionnaires were given to respondents who were tourists. Based on the research, it can be seen that tourists preferences for accommodation landscapes based on ornamental flower plants are higher than leaf ornamental plants, fruit trees, bonsai plants, and palm plants. Therefore, in the accommodation landscape on Gili Meno it is necessary to increase the number of plant groups favored by tourists in the form of ornamental flower plants.